DEVELOPMENT OF LUDIC COMPETENCE QUESTIONNAIRE (LCQ) - Kobzieva, Iuliia; Gordiienko-Mytrofanova, Iia; Zuiev, Ihor; Sauta, Serhii (PSYCHOLOGICAL JOURNAL, 2019)
The article describes the method of measuring ludic competence designed by the authors. Development of ludic competence depends on playfulness which is a stable personality trait. Playfulness is defined as a person’s creative adaptation to the reality of their own “Self” (individual identity) and to the reality of the World (social identity), i.e. every difficult situation can be faced as a challenge, rather than a threat. The article describes the questionnaire design process and its psychometric verification. The authors define the components/scales of ludic competence/playfulness questionnaire using a new psycholinguistic approach. This approach is based on the method of describing psycholinguistic meanings in order to single out basic parameters of ludic competence/playfulness with the help of psychological and linguistic instruments. The scales of the questionnaire reflect a number of conceptual parameters that describe the essence of ludic competence/playfulness: sensitivity, sense of humour, imagination, ease, flirting, impishness, fugue. The structural validity of the questionnaire is justified by analyzing correlation between different scales of Playfulness and scales of emotional intelligence test, questionnaire of humour styles, and self-actualization test. The analysis revealed the strongest correlation between four components: Sensitivity, Ease, Flirting, and Impishness. The questionnaire was subject to standardization and test norms were generated. A high score means optimal development of Playfulness for successful social functioning. A medium score means sufficient development, and a low score shows the deficit of this quality. Factor analysis revealed two latent factors of Playfulness that reflect two opposite tendencies in the questionnaire: Creative communicative susceptibility and Joyful impishness. The questionnaire can be used to measure the development of only one component or the general level of ludic competence/playfulness. The questionnaire is meant to test young examinees, both for individual or group work, as part of counselling and coaching sessions, therapy, or scientific research.